Reliability evaluation of power systems considering restructuring and renewable generators - Mehrtash, Amir (2013)
In the current power systems, some new problems have emerged regarding system reliability management due to system restructuring and the addition of renewable power generators. Because of intermittent and uncertain behaviors of renewable sources, and separation of generation system into different companies, the procedure of reliability evaluation becomes more complicated. The reliability techniques should be improved for applying in the new environment. This paper proposes an equivalent multistate generation provider (EMGP) to represent generation companies with both wind and conventional generating units. A novel approach is proposed to determine the deliverable capacity probability table (DCPT) of the equivalent multistate transmission provider (EMTP) which represents the transmission network capacity. This technique significantly reduces computation burden when both load and supply are subject to change in a power system. The proposed approaches are applied to simulate a modified IEEE Reliability Test System (RTS), and the results are compared with those from the existing techniques.